Peru : Third Review and Inflation Consultation Under the Stand-By Arrangement and Request for Waiver of Applicability of Performance Criteria; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Peru. (IMF Staff Country Reports; Country Report, 2008)
This paper discusses key findings of the Third Review for Peru and Inflation Consultation Under the Stand-By Arrangement. All performance criteria for end-December 2007 and end-March 2008 were observed, but inflation in March exceeded the upper limit of the program's consultation band around the official inflation target range. The end-March structural benchmark was observed and progress has been made on end-June benchmarks. The outlook for 2008 remains favorable, with the economy continuing its strong momentum, as downside global risks are buffered by improvements in fundamentals and prudent policies.